Will intragroup comparison increase pro-environmental behavior? - Wong, Hui Wen (2015)
As environmental issues are fast becoming pressing concerns among the nations, national leaders, environmentalists, and psychologists are looking into ways to salvage the conditions of Earth. Environmental education (EE) is the primary channel that is used in increase pro-environmental behaviors among people. However, the gap between environmental attitudes and actual pro-environmental behavior has suggested that the effectiveness of EE may be limited. Therefore, psychologists are now looking into the possibilities of using social influences to invoke change in environmental behavior. The effect of intragroup comparison on pro-environmental behavior was examined in the present study. The study hypothesized that individuals who received negative intragroup comparison feedback regarding their personal environmental impact in relation to their in-group’s would increase their engagement in pro-environmental behavior. 40 participants were recruited and assigned to positive comparison feedback, negative comparison feedback, or no feedback condition. Measurement of subjects’ engagement in pro-environmental behaviors was taken at two time period, one week apart. No significant result was found to support the predicted change in individual’s pro-environmental behavior after receiving negative intragroup comparison feedback, despite controlling for level of identification with the in-group and pro-environmental scores on the first session. Though the results were statistically insignificant, they revealed a pattern that was going in the direction of the study’s prediction, suggesting that intragroup comparison might still play a role in influencing pro-environmental behaviors. Therefore, despite the insignificant results found in the present study, the effect of intragroup comparison on pro-environmental behavior may still be worthy for further examination.